Growth rates of coral reefs peaked at 25 °C through the Holocene - Tonya Macedo; Robert van Woesik (PLoS ONE, 2026)
For millennia, corals have built coral-reef structures upon the remains of past generations of coral skeletons, forming the world’s most diverse marine ecosystems. Yet, ocean warming and regional and local disturbances are reducing the capacity of coral reefs to grow and keep pace with sea-level rise. Understanding which environmental and climatic conditions influenced reef growth in the past, when human populations were small, may help us understand how reefs respond to contemporary environmental changes. Using coral cores dating back 11,700 calibrated years before present (yr BP) from 291 sites across the Pacific, Indian, and Atlantic Oceans, we examined the relationships between seven environmental and climatic variables and coral-reef growth using a spatial-temporal Bayesian mixed model and a deep-learning neural-network analysis. Our results show a positive relationship between the rate of change in sea level and reef growth. Reef growth responded nonlinearly to sea-surface temperature, peaking at ~25 °C, during the Holocene Thermal Maximum, between ~7,000 and ~5,500 yrs BP. During this period, atmospheric carbon dioxide (CO 2 ) concentrations were ~325 parts per million (ppm) by volume. Our findings reveal that atmospheric CO 2 levels currently exceeding 335 ppm, combined with sea-surface temperatures and modern marine heatwaves, are less than optimal for contemporary coral-reef growth, inhibiting their ability to keep pace with sea-level rise.